The Role of Shared Decision-Making in Shaping Intent to Access Services for Adolescents in Protective Custody - Beal, Sarah J. (Child Care Pract, 2018)
Including children in protective custody (e.g., foster care) in legal decisions positively impacts their perceptions of the legal system, with giving youth a voice being particularly important. Studies have primarily focused on including young people in legal processes; however, for adolescents in protective custody, decisions about living arrangements, education, and long-term planning are made outside the courtroom, with ramifications for young people and their perceptions of both legal and child protection systems. This study looks at such decision making using existing data from 151 adolescents who were ages 16–20 and had been in child welfare protective custody for at least 12 months. During in-person interviews we assessed their desired amount of involvement in a recent decision and their perceptions of their actual involvement. Youth named other individuals involved in decision-making. Data were coded and analysed to identify discrepancies in young people’s perceptions of desired and actual levels of involvement. Results indicate that while the majority of adolescents (96%) are participating in decision-making, they generally desire more involvement in decisions made (64%). Only 7% of youth reported that their level of personal involvement and the involvement of others matched what they desired. The most common individuals identified in a decision made were child protection workers, legal professionals, and caregivers or family members. These findings enhance the existing literature by highlighting the unique issues related to giving young people in protective custody a voice, and provide an empirical foundation for guiding policies around who to involve in every-day decisions made for young people preparing for emancipation from protective custody.